Method of replacing the variables for generalized symmetry of the D'Alembert equation - Gennadii A. Kotel'nikov (International Journal of Mathematics and Mathematical Sciences)
We show that by the generalized understanding of symmetry, the D'Alembert equation for one component field is invariant with respect to arbitrary reversible coordinate transformations.